Gambaran Perilaku Pemeliharaan Kebersihan Gigi dan Mulut pada Masyarakat di Kecamatan Limboto Barat Kabupaten Gorontalo - Mohammad Zulkarnain; Faisal Idrus (Gorontalo Journal of Public Health, 2022)
Dental and oral health care is the maintenance of the teeth and mouth of leftovers and other droppings that are inside the mouth for the purpose of keeping teeth healthy. The research is aimed at getting a picture of dental and oral hygiene behaviors with the limboto district west of gorontalo. The analysis USES an independent variable, which is dental hygiene behavior. The dependent variable of society. The sample of this study is a teenager living in the west limboto district. Student observational-analtic with a cross-sectional research design. Study is conducted on 378 samples. For research identification using multistage random side methods, this study was carried out in 10 villages. Hamulo's village, hutabohu, yosonegoro, padengo, daenaa, ombulo, pone, huidu, northern huidu. Data collection was done by distributing questionnaires. According to studies the number of respondents who brush their teeth twice or more a day with the number of those who do 345 (91%) and the least one who has done an 8 (8%), the correct number of those who pick time to brush their teeth is that most respondents choose morning after breakfast and night before going to bed with 310 (82%). The number of those who chose to visit the dentist at least once a month was 351 (93%), and the least likely were confused by deng